Interview of Margaret Karembu Director, ISAAA Africenter, Kenya - Karembu, M. (International Livestock Research Institute, 2014)
Interviews of selected participant; views from the Regional Experts Workshop on Industrial Effluents Management in East Africa held on 19-20 May 2014, Ethiopia